Supporting Womens Agro-Enterprises in Africa with ICT : A Feasibility Study in Zambia and Kenya - World Bank (Washington, DC, 2015)
A new generation of information and communication technologies (ICTs) is finding a small foothold among poor, small-scale farmers in developing countries. Even so, many barriers still prevent poor rural people from accessing, using, and benefiting from new ICT tools and platforms, and those barriers are arguably higher for rural women. The relationship between gender and agriculture has been studied intensively over the years, and many agricultural interventions now include gender as a crosscutting issue or mainstream gender throughout their operations. Studies of the relationship between gender and the use of ICTs in agriculture have started to appear only quite recently, however. The Africa Region of the World Bank views ICTs as potentially transformative technology for rural development and seeks to incorporate the use of ICTs throughout its portfolio of projects. The present study was designed to examine the feasibility of integrating ICTs into two large investment programs: the Irrigation Development and Support Project (IDSP) in Zambia and the Kenya Agricultural Productivity and Agribusiness Project (KAPAP). The specifi c goal was to examine how ICT-based interventions might be designed to strengthen women s participation in commodity value chains under the two projects.